Effects of temperature on the development, behaviour and geography of blowflies in a forensic context - Richards, Cameron Spencer (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2008)
The development of immature insects is commonly employed in forensic investigations to estimate time of death, or postmortem interval (PMI), of a corpse on which they are feeding. The bulk of this thesis focuses on factors influencing the accuracy of developmental data, and exploring how and why developmental data differ between studies involving the same species, and between different species. Because carrion feeding insects are ectotherms, temperature may be expected to significantly influence their behaviour, development and distribution, and the remainder of the thesis therefore focuses on the thermal biology and geographical distribution of seven forensically important blowflies. The species include Chrysomya albiceps, C. putoria, C. chloropyga, C. megacephala, C. marginalis, C. inclinata and Calliphora croceipalpis. A robust experimental design for estimating developmental models is outlined and tested. It is recommended that forensic entomologists should involve at least six constant temperatures, starting at about 7Â°C above the relevant developmental zero (D0) and going to about 10Â°C above the upper critical temperature, and a temporal sampling interval with a relative precision of about 10%. Using this design, focused experiments consistently provided the most reliable developmental data, while data pooled from different studies yielded inconsistent results. Similarly, developmental data from closely related species differed significantly, and surprisingly so did developmental data from different populations of the same species. Possible explanations for the latter lay in the different methods of data collection but only temporal sampling resolution had a direct influence on the accuracy of developmental data. Consequently, disparities in such data were primarily ascribed to genetic differences and phenotypic plasticity. Comparisons between numerous thermal thresholds of larvae, pupae and adults support this conclusion and suggest a phylogenetic component to the thermal biology of blowflies. Further comparisons were made between these temperature thresholds and the distributions of blowfly species present on two rhinoceros carcasses. These comparisons suggest that blowfly larvae with high upper lethal temperature thresholds dominate in interspecific competition in favorable thermal environments by raising maggot mass temperature above the thresholds of other carrion-feeding blowflies, through maggot-generated heat. Bioclimatic modeling using maximum entropy analysis provided a successful means of predicting whether a species is likely to occur in an area, and whether it would therefore be expected in a local carcass community. It also showed that temperature was less important than moisture in shaping the geographical distribution of African carrion blowflies. Based on these results, several recommendations are made for the practice of forensic entomology.
Keywords: Blowflies; Blowflies -- South Africa; Diptera -- South Africa; Insects -- Development Insects -- Behavior; Forensic entomology